The effect of strengthening the prerequisite knowledge on student learning outcomes on the topic of values ​​and eigenvectors - N. Siregar; Irma Novalinda (Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study to determine the effect of strengthening prerequisite knowledge on students' achievement via and seeing students' perspectives on improving prerequisite knowledge. The research method was the Pre-Experiment, and the research sample was students of physics education on the 3rd semester in UGN Padangsidimpuan, totaling ten people. The instrument for collecting students' achievement is an essay test given to the pretest and posttest, and the device for managing students' perspectives on strengthening prerequisite knowledge is a questionnaire. Data analysis techniques for achievement were used non-parametric statistical tests with the Wilcoxon test and N-Gain, while the students' perspectives were analyzing through descriptive qualitative. This study's results indicate that there is a significant effect of strengthening the prerequisite knowledge on students' achievement, with a significance value of the Wilcoxon test count of 0.005. N-Gain obtained 0.74 in the high category. The results of the questionnaire distribution showed a positive perspective on strengthening prerequisite knowledge compared to previous learning. This medium indicates that there is an effect of enhancing prerequisite knowledge on students' achievement, an increase in achievement, and positive student perspectives on strengthening prerequisite knowledge.